The CFO's Playbook: Strategic Financial Management For Competitive Advantage - Rheza Pratama; Iin Safariah; Muhammad Anas (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study explores the impact of Strategic Financial Management and Financial Planning and Analysis on Competitive Advantage within Bank Syariah Indonesia KC Ternate, with a focus on the mediating role of Financial Decision-Making Quality. Utilizing a quantitative research design, data was collected from 70 customers through structured questionnaires and analyzed using Smart PLS (Partial Least Squares). The findings reveal significant direct effects of Strategic Financial Management and Financial Planning and Analysis on Competitive Advantage, with coefficients of 0.50 and 0.32, respectively. Additionally, the analysis uncovers significant indirect effects where both Strategic Financial Management and Financial Planning and Analysis influence Competitive Advantage through improved Financial Decision-Making Quality, with coefficients of 0.25 and 0.21, respectively. These results underscore the critical role of high-quality financial decision-making in enhancing the competitive advantage of the bank, highlighting the need for effective strategic financial management and planning to drive organizational success.